Impact of protease supplementation on growth performance and economic efficiency in broiler chicks. - Abdulmajid, Saman; Soran Hussein Suliaman (University of Thi-Qar Journal of agricultural research, 2025)
This study was conducted to determine the effect of protease enzyme supplementation on improvement in growth performance and economic returns for broiler chicks fed standard and low-protein diets. A total of 396 one-day-old Ross 308 broiler chicks were randomly allotted to nine dietary treatments according to a 3 × 3 factorial arrangement that consisted of three basal rations, the standard broiler ration (SBR), a low-protein ration with 4% less protein (4% LPR), and a low-protein ration with 8% less protein (8% LPR) each supplemented with 0, 125, or 250 mg/kg of exogenous protease enzyme (JEFO, Canada). Chicks were raised over 35 days of phased feeding (pre-starter, starter, finisher) and were evaluated for changes in body weight, body weight gain, feed intake, feed conversion ratio (FCR), and economic efficiency (EEF). The results showed that protease supplementation had no effect on body weight in the early phases but enhanced (p < 0.05) body weight in the later stages, especially in T6 (4% LPR + 250 mg/kg protease), which performed nearly similar to the control group (T1). Feed intake increased with enzyme supplementation, particularly in T8 (8% LPR + 125 mg/kg). The FCR was greatly enhanced by protease supplementation, much like in T6. From the economic analysis, it transpired that treatment T6 yielded the highest EEF (1.11), the same as the control, that is, the herbal medication; however, it is statistically higher than the unsupplemented LPR group (T4). Thus, it may be inferred that supplementation of the diet with protease would help reduce crude protein levels without the growth or profit of broilers being unduly affected, hence aiding sustainable poultry nutrition. Use of protease is a means of reducing feed cost and nitrogen emissions while maintaining production efficiency.